Heat Partition Coefficient and Temperature Variation during Engagement in Multi-disc Clutch - Yuan Yuelan; Chen Man; Li Shihong (Jixie chuandong)
A finite element model of heat conduction process between the friction components in a multi-disc clutch is setup. With coupled algorithm， the heat partition coefficient between friction components in multi-disc clutch and the temperature variations in the cases of engagement with the same initial rotating speeds and the same time are studied. The temperature field is non-dimensionalized and compared， the results show that， during both cases of engagement， the heat partition coefficients are higher than that of sliding with fixed rotating speed and approach to 1 rapidly at the end of engagement. The contact pressure in the case of engagement with the same initial rotating speed makes influence on its peak temperature， and thus there exists a critical pressure with which the lowest peak temperature can be obtained. This critical pressure benefits the thermal stability of the multi-disc clutch. In the case of engagement with the same time， the heat partition process will not change even though the contact pressure is changed， and the variation processes of the dimensionless temperature will not be changed neither. This will facilitate the thermal status estimation of the clutch.